(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article is devoted to the semantic and structural peculiarities of one group of Ukrainian one-phrase charm exorcist texts – texts-narrations. These peculiarities are provoked by communicative task and magic function of these texts. Charm exorcist narrations are represented definite psychological peculiarities of speaker.